Additional evaluations show that specific BWA‐aln settings still outperform BWA‐mem for ancient DNA data alignment. Issue 24 (17th December 2021) - Oliva, Adrien; Tobler, Raymond; Llamas, Bastien; Souilmi, Yassine
Abstract : Xu et al. (2021) recently recommended a new parameterization of BWA‐mem as a superior alternative to the widely‐used BWA‐aln algorithm to map ancient DNA sequencing data. Here, we compare the BWA‐mem parameterization recommended by Xu et al. with the best‐performing alignment methods determined in the recent benchmarks of Oliva and colleagues (2021), demonstrating that BWA‐aln is still the gold‐standard for ancient DNA read alignment .